TEKST, PARATEKST, PRZESUNIĘCIA INTERPRETACYJNE W POLSKICH WYDANIACH PRZYGÓD FANDORINA (CZĘŚĆ 1: PARATEKSTY GRAFICZNE ) - Kaźmierczak, Marta (Przegląd Rusycystyczny, 2017)
The paper brings an analysis of interpretational shifts connected with elimination, addition or substitution of various paratexts in translation. The study is based on Boris Akunin’s historical detective novels in Polish editions, as compared to original ones. In the first part, the author focuses on illustrations, their communicative and associative potential. (Other paratexts will be further discussed with regard to their functions: identifying, hermeneutic, informative and commercial). The shifts in paratextual use in the translated editions are interpreted in terms of the ambiguous tension between features of literary and genre fiction displayed by Akunin’s novels. Conclusions about the overall strategy of the publisher and its consequences for reception are ventured. In particular, Polish paratexts testify to the novels’ gravitating more obviously towards mass literature in the target context.